Prolific Inventor Productivity and Mobility: A Western/Asian com-parison. Evidence from US Patent Data for 12 Countries - Christian Le Bas; William Latham; Dmitry Volodin (Comparative Economic Research, 2012)
This paper provides new insights into the role of individual inventors in the innovation process. Individuals are central in this creative process because innovation is not simply a product of firms and organizations; it requires individual creativity (Rothaermel and Hess, 2007). We focus our analysis on prolific inventors (a rich sub category of inventors) because they contribute so hugely to national invention totals (Le Bas et al., 2010) and tend to produce inventions that have more economic value (Gambardella et al., 2005; Gay et al., 2008). Converging empirical evidence has established the significance of prolific inventors (Ernst et al., 2000). Previous studies of prolific (or “key”) inventors have focused more on the firms in which they work or on the industries in which the firms operate. Narin and Breitzman’s (1995) seminal work on the topic is based on an analysis of only four firms in a single sector and a recent paper by Pilkington et al. (2009) uses only two firms. In contrast to these studies on small samples, we use a very large data set which includes thousands of inventors in thousands of firms from several countries.